Opportunity Knocks: Organic Chemistry for Fragment‐Based Drug Discovery (FBDD). Issue 2 (3rd November 2015) - Murray, Christopher W.; Rees, David C.
Abstract : What's a good fragment? Fragment‐based drug discovery is well‐established within many pharmaceutical, biotech, and academic institutions for generating new drugs. In this Essay, the opportunities and challenges for organic chemists to design and synthesize new fragments are described.